Exploring the adoption of Schwartz Center Rounds as an organisational innovation to improve staff well-being in England, 2009–2015. Issue 1 (5th January 2017) - Robert, Glenn; Philippou, Julia; Leamy, Mary; Reynolds, Ellie; Ross, Shilpa; Bennett, Laura; Taylor, Cath; Shuldham, Caroline; Maben, Jill
Abstract : Objectives: Schwartz Center Rounds ('Rounds') are a multidisciplinary forum in which healthcare staff within an organisation discuss the psychological, emotional and social challenges associated with their work in a confidential and safe environment. Implemented in over 375 North American organisations, since 2009, they have been increasingly adopted in England. This study aimed to establish how many and what types of organisations have adopted Rounds in England, and to explore why they did so. Setting: Public healthcare organisations in England. Participants: Secondary data analysis was used to map and profile all 116 public healthcare organisations that had adopted Rounds in England by July 2015. Semistructured telephone interviews were conducted with 45 Round coordinators within adopting organisations. Results: The rate of adoption increased after a major national report in 2013. Rounds were typically adopted in order to improve staff well-being. Adopting organisations scored better on staff engagement than non-adopters; among adopting organisations, those performing better on patient experience were more likely to adopt earlier. Most adoption decision-making processes were straightforward. A confluence of factors—a generally favourable set of innovation attributes (including low cost), advocacy from opinion leaders in different professional networks, active dissemination by change agents and a felt need to be seen to be addressing staff well-being—initially led to Rounds being seen as 'an idea whose time had come'. More recent adoption patterns have been shaped by the timing of charitable and other agency funding in specific geographical areas and sectors, as well as several forms of 'mimetic pressure'. Conclusions: The innate attributes of Rounds, favourable circumstances and the cumulative impact of a sequence of distinct informal and formal social processes have shaped the pattern of their adoption in England.